Itô-Henstock integral and Itô's formula for the operator-valued stochastic process - Labendia, Mhelmar A (Archīum Ateneo, 2018)
In this paper, we introduce the Itô-Henstock integral of an operator-valued stochastic process and formulate a version of Itô’s formula.